2016
DOI: 10.5455/njppp.2015.5.2108201585
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index with primary and secondary infertility among infertile women in Mangalore: A cross-sectional study

Abstract: Background: Studies have shown that overweight and underweight can contribute to fertility problems. There is a significant paucity of data in the Indian context regarding the effect of body mass index (BMI) on infertility in women. Aims and Objective: To find the association of BMI with primary and secondary infertility among infertile women in Mangalore. Materials and Methods: This cross-sectional study included 204 infertile women (18-45 years) from a tertiary care hospital in Mangalore. Primary and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Among infertile women, 68% had primary infertility and 32% had secondary infertility. This was concurrent to the study done by Dhandapani K et al, which found that 67% had primary infertility and 33% had secondary infertility (Dhandapani et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Among infertile women, 68% had primary infertility and 32% had secondary infertility. This was concurrent to the study done by Dhandapani K et al, which found that 67% had primary infertility and 33% had secondary infertility (Dhandapani et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…According to the findings of different studies, reproductive system disorders like sexually transmitted disease and endometrial and ovarian dysfunction, genetic factor, age, alcohol consumption, smoking, obesity, irregular menstrual cycle, age at menarche, age at marriage, and dysmenorrhea are found to be factors affecting infertility [3,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperprolactinemia can interrupt ovarian physiology at various levels, including steroidogenesis, follicular maturation and ovulation, the process of luteinisation and corpus luteum function [7].…”
Section: Prolactinmentioning
confidence: 99%